Electrochemical Treatment of Water Polluted with β-Lactam Antibiotics. - Giraldo Aguirre, A. L.; Erazo Erazo, E. D.; Flórez Acosta, O. A.; Serna Galvis, E. A.; Torres Palma, R. A. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Oxacillin (OXA), cloxacillin (CLX) and Dicloxacillin (DCX) are β-lactam antibiotics, used to treat infections caused by gram-positive and gram-negative microorganisms, which can reach aquatic systems due to improper disposal or deficient water system treatments, thus representing a risk to the environment. With this work, the degradation of these -lactam antibiotics was investigated by anodic oxidation using a DSA anode Ti/IrO2. An experimental design with variables assessing current density, supporting electrolyte, and the concentration of substance, allowed to evaluate the most favorable conditions for the degradation of the β-lactams tested. The best eciencies in terms of pollutant and antibiotic activity removals, were obtained at high current level (121 mA) and average concentration of NaCl (0.225 mol L